Recycling spent lithium-ion batteries using a mechanochemical approach - Mengmeng Wang; Kang Liu; Jiadong Yu; Cong-Cong Zhang; Zhiyuan Zhang; Quanyin Tan (Circular Economy, 2022)
Under the goal of global sustainable development, the new energy vehicle industry is evolving rapidly, leading to a proliferation of spent lithium-ion batteries (LIBs). The recycling of LIBs is key to the sustainable development of the new energy industry, which is consistent with the concept of circular economy as well. And the green extraction of critical metals is the core part of the development. As an alternative to traditional pyrometallurgy and hydrometallurgy, emerging mechanochemical technology provides a new approach for high efficiency and green recycling of critical metals from spent LIBs, as it has the advantages of easy operation, flexibility, and short processing time. This article reviews the state of the art of mechanochemical technology in the recycling of critical metals from spent LIBs. Based on numerous practices, a framework including mechanochemical activation, organic reaction, inorganic reaction, redox reaction, gas-solid reaction, and solid-phase synthesis was constructed. These practices have proved that mechanochemical technology can provide a greener and more sustainable solution for recycling critical metals from spent LIBs. The metals can be transformed into high-value metal products at room temperature and under ordinary pressure, leading to efficient recycling of critical metals and significant reduction of wastes.